Hearing and Patient Satisfaction Among 19 Patients Who Received Implants Intended for Hybrid Hearing: A Two-Year Follow-Up. Issue 5 (September 2015) - Erixon, Elsa; Rask-Andersen, Helge
Abstract : Objectives: To measure patient satisfaction and correlate to hearing results in partially deaf patients, after hearing preservation cochlear implant surgery with hybrid hearing strategy, and to evaluate the stability of residual low-frequency hearing (LFH) over time. Design: A patient satisfaction survey and a retrospective, 2-year follow-up journal study. Nineteen partially deaf patients intended for hybrid hearing responded to a questionnaire when they had used their cochlear implants for at least a year. The questionnaire consisted of the International Outcome Inventory for Hearing Aids, EuroQol Group visual analogue scale and nine questions about hybrid hearing. Pure-tone audiometry, monosyllables, and hearing in noise test results from the patients' medical records were evaluated and compared with the results from the patient satisfaction survey. Results: All of the patients were satisfied with their CIs. The mean International Outcome Inventory for Hearing Aids score was 29. The CIs provided a major contribution to the speech comprehension of these partially deaf patients. Two years after surgery, the patients' mean binaural score on tests of monosyllables was 58%, and the mean signal to noise ratio was 4.6 dB. We observed ongoing deteriorations in the residual hearing of the operated ears that surpassed the deteriorations observed in the contralateral ears. One month after surgery, the LFH loss (125–500 Hz) was 17 dB, and after 2 years, this loss was 24 dB compared with 5 dB in the nonoperated ear. There were no significant correlations between preserved LFH and patient satisfaction or speech perception results. Conclusions: Electric stimulation provided a major contribution to speech comprehension of partially deaf patients. The gain reached in speech understanding widely exceeded the downside in losing some residual hearing. All the patients showed a high degree of satisfaction with their CIs regardless of varying hearing preservation. Abstract : Electric stimulation contributes to speech perception in partially deaf patients. Here patient satisfaction after cochlear implantation with hybrid hearing strategy is compared to preserved hearing and also to monosyllables and hearing in noise test results. There is an ongoing deterioration of residual hearing, but the gain reached in speech discrimination while the patients receive cochlear implants widely exceeds the downside in losing some residual hearing. All the patients were very satisfied with their implants.Supplemental Digital Content is available in the text.